SMEs Branding: The Interaction of Entrepreneurial Orientation - Alanazi, Tawfeeq Mohammed (Journal of Research in Marketing (ISSN: 2292-9355), 2018)
The purpose of this research is to find the extended impact and interaction of entrepreneurial orientation (EO) as a moderator variable on the relationships between brand strategy (specifically brand orientation, brand identity and brand distinctiveness) and brand performance. Retroactively, the direct relationship between brand strategy and brand performance should be elucidated. The basic methodology of this research is positivism, specifically a deductive approach to which really on previous understanding and propositions that extracted from previous works. A well-designed and tested questionnaire is used to collect data for this research, and the data is analysed by applying the partial least squares technique, which is a method of structural equation modelling technique of analysis. Prior to this step, a confirmatory factor analysis is performed to inspect measurement constructs. The result indicates a significant positive and direct impact of brand orientation and brand identity on performance of brand where brand distinctiveness has no impact. On the other side, when entrepreneurial orientation is interactive as a moderator factor, the relationships between brand orientation, brand identity and brand performance increase and become stronger. Previous research and studies elucidated the impact of various factors of brand strategy on brand performance. However, entrepreneurial orientation as a moderator variable has not been examined. What makes this research different from others is the practical investigation and the examination of the impact of entrepreneurial orientation as an important factor of brand strategy in SMEs